87 Effect of addition of short and medium chain fatty acids monoglycerides in Holstein steers fed straw and concentrates. (7th December 2018) - Miranda, L; Serrano, C; García, M; González, V; Medel, P
Abstract: A total of 100 Holstein male steers (263.8 ± 14.1kg), were used to evaluate the effect of the addition of short and medium chain fatty acids monoglycerides (SMCFA-MG) on productivity and carcass quality. There were two treatments: 1) Control diet(C), a mash corn and barley-based concentrate and straw ad libitum, 2) C+3, 5kg/t of a SMCFA-MG (M). Steers were distributed at random in 4 pens of 25 steers, and there were 2 replicates/treatment. Trial lasted 129d, and steers were weighted individually at 35, 70, 105 and 129d. Concentrate consumption per replicate was taken daily. Individual weight and growth were analyzed through an ANOVA; model included initial bodyweight as covariate, and treatment as main effect. Body weight evolution was also analyzed by repeated means. Time effect was significant (P < 0.01), and there was an interaction time*treatment (P=0.038). Both treatments showed similar weight at 35 and 70d, but steers fed C showed higher body weight at 105 and 129d (403, 8 vs 410, 8 and 438, 6 vs 446, 6, for C and M respectively, P=0.035 and 0.046). In growth, there were no differences between treatments from 0-70d, but from 70–105, steers fed M showed higher growth (1328 vs 1493g/d for C and M respectively, P=0.001), with no differences in the period 105–129. For the whole period, differences in growth were significant (1355 vs 1417g/d for C and M respectively, P=0.046). Also, numerically there were not differences in concentrate feed intake along the experiment (7994 vs 7873g/d), but steers fed C showed numerically lower concentrate feed conversion (5.892 vs 5.512kg/kg for C and M respectively). There were no differences in carcass yield (51.37 vs 51.45% for C and M, P=0.855). It is concluded that the supplementation of SMCFA-MG in Holstein steers improved growth from 70 to 105d, allowing a 1, 8% higher final weight, without effect on carcass yield.